2006
DOI: 10.1148/rg.264055144
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bowel and Mesenteric Blunt Trauma with Multidetector CT

Abstract: Bowel and mesenteric injuries are detected in 5% of blunt abdominal trauma patients at laparotomy. Computed tomography (CT) has been shown to be accurate for the diagnosis of bowel and mesenteric injuries and is the diagnostic test of choice in the evaluation of blunt abdominal trauma in hemodynamically stable patients. Specific CT findings of bowel and mesenteric injuries include bowel wall defect, intraperitoneal and mesenteric air, intraperitoneal extraluminal contrast material, extravasation of contrast ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
161
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(179 citation statements)
references
References 28 publications
(24 reference statements)
4
161
1
Order By: Relevance
“…However this was seen in only 2 of 25 patients in a study by Killeen et al, as most patients have inadequate bowel wall opacification because of the often urgent nature of the CT scan examination [12]. While in a study by Brofman et al [13] it was seen in only 3/54 (6%) of patients.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…However this was seen in only 2 of 25 patients in a study by Killeen et al, as most patients have inadequate bowel wall opacification because of the often urgent nature of the CT scan examination [12]. While in a study by Brofman et al [13] it was seen in only 3/54 (6%) of patients.…”
Section: Discussionmentioning
confidence: 93%
“…Bowel wall discontinuity was seen in 4/54 (7%) patients in a study by Brofman et al They postulated that the relative infrequency of observations of this feature is likely due to small size of the discontinuities, which are evident at surgery only with careful inspection [13].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Earlier studies reporting relatively lower rate of correct identification of mesenteric injuries largely predated MDCT. Currently, evidence from multiple recent studies reported better diagnostic accuracy with a sensitivity ranging from 69-95% and a specificity of 94-100% [7].…”
Section: Discussionmentioning
confidence: 99%